PENGARUH BABY MASSAGE TERHADAP KUANTITAS TIDUR BAYI USIA 3-6 BULAN DI ATHA MOM AND BABY CARE LUMAJANG - Saputri, Hindun Wasaynab Dian Cahya; Wijayanti, Tut Rayani Aksohini; Purwanti, Anik Sri (NHM PRESS, 2024)
The quantity of sleep in infants aged 3-6 months is an essential aspect of their development and well-being, as well as for their families. During this stage, infants undergo rapid changes in their sleep patterns, and parents often face challenges in ensuring that their babies sleep soundly. This study aims to determine the Influence of Baby Massage on the Quantity of Sleep in Infants Aged 3-6 months at Atha Mom And Baby Care Lumajang. The type of research to be used in this study is pre-experimental design using the pretest and posttest one-group design method. The sample of this study consists of 20 infants aged 3-6 months using total sampling technique. From the research results, it was found that the majority of respondents had poor sleep quality, with 12 respondents (60%) before receiving Baby Massage, and those with good sleep quality were 18 respondents (90%) after receiving Baby Massage. From the analysis table using the Wilcoxon test, the α value obtained was 0.002, which means that α <0.05, and it can be concluded that there is an Influence of Baby Massage on the Quantity of Sleep in Infants Aged 3-6 months at Atha Mom And Baby Care Lumajang. The increase in sleep quantity in infants who received massage is caused by an increase in the secretion of serotonin produced during the massage. Serotonin is the main neurotransmitter associated with the onset of sleep by suppressing the activity of the reticular activating system and other brain activities.